2015
DOI: 10.1155/2015/104818
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Injury in Children with Unoperated Congenital Heart Diseases

Abstract: Background. Children with congenital heart diseases (CHDs) may have a risk of developing myocardial injury caused by volume and pressure overload. Objective. To evaluate the incidence of myocardial injury in children with cyanotic and acyanotic CHDs using cTnI assay and to correlate it with different hemodynamic parameters. Methods. This study included 80 children with CHDs (40 acyanotic and 40 cyanotic) as well as 40 healthy children (control group). Serum cTnI levels were measured for patients and control. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…After taking ethical clearance from the institute ethics committee and informed consent from the parents/caregivers of the children, a total of 83 children (55 cases and 28 age matched healthy controls) between the ages of 6 months to 5 years were enrolled. A study conducted by Hafez, et al [6] showed the prevalence of myocardial injury in 82.5% acyanotic congenital heart disease patients. By taking into account 90% confidence level and 10% margin of error, the sample size calculated using online sample size calculator [http:// www.raosoft.com/samplesize.html].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After taking ethical clearance from the institute ethics committee and informed consent from the parents/caregivers of the children, a total of 83 children (55 cases and 28 age matched healthy controls) between the ages of 6 months to 5 years were enrolled. A study conducted by Hafez, et al [6] showed the prevalence of myocardial injury in 82.5% acyanotic congenital heart disease patients. By taking into account 90% confidence level and 10% margin of error, the sample size calculated using online sample size calculator [http:// www.raosoft.com/samplesize.html].…”
Section: Discussionmentioning
confidence: 99%
“…In our study myocardial injury was evidenced by higher levels of hs-cTnT in 80.4% of the cases. A study by Hafez, et al [6] in Egypt elicited the evidence of myocardial injury in unoperated congenital heart disease. Increased Cardiac troponin-I was found in 64 out of 80 (80%) children with CHD.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on cTnI and other biomarkers of CHD are limited especially in developing countries, however some studies had developed in different target population, as in the study done by the Egyptian authors Hafez et al (2015) (27) who studied 40 children (1 month to 12 years) with acyanotic CHD, 40 children with cyanotic CHD and 40 healthy children. They reported that cTnI was significantly higher in diseased group compared to control group and that the sensitivity of the test was 80%.…”
Section: This Can Be Explained By What Was Previously Published By Gamentioning
confidence: 99%
“…Hafez et collaborators used cTnI in evaluating the children with cyanotic and acyanotic heart disease and proved that the cTnI was significantly increased in both type of malformations (p<0.05) and has a significant correlation with oxygen saturation, ejection fraction and pulmonary to systemic blood flow (Qp/Qs) and pulmonary to systemic arterial pressure (Pp/Ps) ratios. The conclusion was that the incidence of myocardial damage in congenital heart disease is high and needs an early detection, for an early treatment, offering a good outcome for the patient [8]. A Scandinavian group report that cTnI is increased in pediatric patients with pressure overload due to aortic coartation and aortic and pulmonic valve stenosis, more than in volume overload due to atrial septal defect(ASD) or patent ductus arteriosus(PDA) and the situation returns to normal after surgical correction.…”
Section: Cardiac Troponinsmentioning
confidence: 99%